Perceptual-cognitive performance of youth soccer players in a 360°-environment – Differences between age groups and performance levels. (March 2022) - Ehmann, Paul; Beavan, Adam; Spielmann, Jan; Mayer, Jan; Altmann, Stefan; Ruf, Ludwig; Rohrmann, Sonja; Irmer, Julien Patrick; Englert, Chris
Abstract: Introduction: An important requirement for soccer players is the accurate and rapid processing of dynamic and complex visual scenes. Therefore, in high-level youth soccer the players' perceptual-cognitive skills are highly relevant from a scientific and practical point of view. The aim of the present study was to investigate differences in perceptual-cognitive performance between youth soccer players of different age groups and soccer performance levels in a dynamic 360°-environment. Methods: In a sample of 292 elite and sub-elite youth soccer players from the age groups U12–U23, perceptual-cognitive skills were assessed using a 360°-multiple object tracking task. An 8 × 2 (age group x performance level) analysis of variance (ANOVA) was conducted to examine the effects of age group and soccer performance level on performance in the task. Results: The analyses revealed a significant main effect of age group. Post hoc analyses showed that youth players belonging to the older age groups (U16, U17, U19, and U23) performed significantly better in the 360°-multiple object tracking task than players of the youngest age group (U12). Yet no significant age-related differences could be found from age group U16 on. Furthermore, there was a significant effect of soccer performance level on the 360°-multiple object tracking performance in favor of the elite players. Significant differences between elite and sub-elite players within the same age group were only present in the highest age groups U19 and U23. Conclusions: The results suggest that in a dynamic 360°-environment highly talented youth soccer players show better perceptual-cognitive performance with increasing age. Furthermore, elite youth players exhibit distinctive perceptual-cognitive abilities particularly at the highest age groups. These findings provide interesting implications for science and practice regarding the perceptual-cognitive skills of talented soccer players and their role in talent development. Highlights: Cognitive functions of youth soccer players assessed with 360°-object tracking task. Cognitive performance of youth soccer players increases with age. Elite players show better cognitive performance than sub-elite players. Differences between elite and sub-elite youth players emerge in older age groups.